(untitled) (Journal of Dhaka Medical College, 2023)
Background/Aims: Acute stroke is one of the leading causes of mortality and morbidity worldwide. The adverse outcome following acute stroke depends not only on severity of the neurological defects but also on other co-morbidities. Associated renal impairment has been found to be a major predictor of different outcome following acute stroke in several studies. The aim of this study was to evaluate the impact of the serum creatinine on the outcome of hospitalized patients after acute stroke. Methods: This was a Prospective cohort study conducted on 100 consecutive adult patients who were admitted in the Neurology department of Dhaka Medical College Hospital following acute stroke during January 2018 to December 2019.The patients were followed up for two weeks after the incident stroke. Results: Among the 100 patients with acute stroke 57(57%) were ischaemic and 43(43%) were haemorrhagic stroke. Mean age(SD) was 60.4(10.6) years. Patients with ischaemic stroke were older compared to haemorrhagic stroke (61.1(9.6); 53.8(9.4) years respectively; p<0.05). The mean (SD) serum creatinine on admission in patients with both types of stroke, who deteriorated or died, were significantly higher than in those who survived. Others predictors of mortality and morbidity in both types of acute stroke were age, gender, hypertension, diabetes mellitus, ischemic heart disease, dyslipidaemia. Conclusions: Patients with impaired renal function had worse outcome after hospitalization in both types of acute stroke. Haemorrhagic stroke, older age, high baseline serum creatinine, hypertension were significantly associated with increased mortality and morbidity following acute stroke. Appropriate measures should be taken to patients with impaired renal function to reduce the mortality and morbidity following acute stroke. J Dhaka Med Coll. 2021; 29(1): 16-23